Tooth enamel nitrogen isotope composition records trophic position: a tool for reconstructing food webs - Jennifer N. Leichliter; Tina Lüdecke; Alan D. Foreman; Nicolas Bourgon; Nicolas N. Duprey; Hubert Vonhof; Viengkeo Souksavatdy; Anne-Marie Bacon; Daniel M. Sigman; Thomas Tütken; Alfredo Martínez-García (Communications Biology, 2023)
Enamel-bound nitrogen isotopes in modern and fossil mammal teeth preserve dietary and trophic level information. This novel geochemical archive can be used to reconstruct trophic niche in ancient ecosystems.